New records of Phylinae (Hemiptera: Heteroptera: Miridae) from the Palaearctic Region - Konstantinov, Fedor V.; Namyatova, Anna A. (Zootaxa, 2008)
The following 62 species of Phylinae are recorded for the first time from various Palaearctic countries: Alloeomimus kurdus (Turkmenistan, Uzbekistan), Aspidacanthus myrmecoides (Mongolia), Hallodapus montandoni (Iran, Uzbekistan, Kyrgyzstan, and Mongolia), Omphalonotus quadriguttatus (Kyrgyzstan), Systellonotus triguttatus (Kazakhstan), Pilophorus cinnamopterus (Kazakhstan and Mongolia), Pilophorus clavatus (Kazakhstan), Pilophorus disjunctus (Kazakhstan), Pilophorus sinuaticollis (Caucasus, Iran, and Mongolia), Amblytylus jani (Morocco), Amblytylus peitho (Kazakhstan, Tajikistan, Turkmenistan, and Uzbekistan), Anonychiella brevicornis (Ukraine, northern Kazakhstan, and Kyrgyzstan), Atractotomimus picturatus (Turkmenistan), Atractotomus magnicornis (Caucasus), Atractotomus morio (Mongolia), Boopidocoris salsolae (Tajikistan), Boopidocoris vitticollis (Mongolia), Camptotylus apanaskevichi (Kazakhstan), Campylomma nigronasutum (Kazakhstan), Chlorillus pictus (Georgia), Compsidolon absinthii (Armenia and Kyrgyzstan), Compsidolon kerzhneri (Mongolia), Conostethus hungaricus (Uzbekistan), Conostethus roseus (Iran), Conostethus venustus (Iran), Criocoris crassicornis (Kazakhstan and Mongolia), Eurycolpus flaveolus (southern part of European Russia, Kazakhstan, and Uzbekistan), Glaucopterum atraphaxidis (Armenia), Hadrophyes sulphurella (northern Kazakhstan), Leucodellus nathaliae (Turkmenistan, Kyrgyzstan, and Uzbekistan), Lepidargyrus muminovi (Uzbekistan), Litoxenus tenellus (Asian part of Kazakhstan and Turkey), Lopidodenus bipunctatus (Tajikistan), Macrotylus dentifer (Iran), Macrotylus dimidiatus (Mongolia), Macrotylus paykullii (Tajikistan), Macrotylus cruciatus (Uzbekistan), Maurodactylus fulvus (Cyprus), Megalocoleus chrysotrichus (Turkmenistan), Megalocoleus dissimilis (Azerbaijan), Megalocoleus lunula (Ukraine), Megalocoleus mellae (Uzbekistan), Megalocoleus molliculus (Tajikistan and Turkmenistan), Megalocoleus tanaceti (Georgia and Uzbekistan), Monocris griseolus (Uzbekistan), Oncotylus vitticeps (Armenia and Turkmenistan), Orthonotus fuscicornis (Asian part of Kazakhstan), Placochilus seladonicus (Armenia), Psallopsis kirgisica (Armenia), Psallus dichrous (Algeria), Psallus henschii (Armenia), Psallus corsicus (Turkey), Salicarus roseri (Georgia), Salicarus urnammu (Armenia), Tuponia kiritshenkoi (Mongolia), Tuponia prasina (Turkmenistan), Tuponia suturalis suturalis (Tajikistan), Tuponia arcufera (Uzbekistan), Tuponia elegans (Armenia), Tytthus pygmaeus (Central Asia), Voruchia vittigera (Central Asia), Voruchiella dubia (Kazakhstan and Uzbekistan).